Motion in microfluidic ratchets. Issue 23 (19th October 2016) - Caballero, D.; Katuri, J.; Samitier, J.; Sánchez, S.
Abstract : In this Focus article we discuss recent advances in the use of ratchet-like geometries in microfluidics which could open new avenues in biomedicine for applications in diagnosis, cancer biology, and bioengineering. Abstract : The ubiquitous random motion of mesoscopic active particles, such as cells, can be "rectified" or directed by embedding the particles in systems containing local and periodic asymmetric cues. Incorporated on lab-on-a-chip devices, these microratchet-like structures can be used to self-propel fluids, transport particles, and direct cell motion in the absence of external power sources. In this Focus article we discuss recent advances in the use of ratchet-like geometries in microfluidics which could open new avenues in biomedicine for applications in diagnosis, cancer biology, and bioengineering.